Passing a Mechanical Aortic Valve With a Short Tip Dilator to Facilitate Aortic Arch Endovascular Branched Repair. (June 2021) - Konstantinou, Nikolaos; Peterss, Sven; Stana, Jan; Rantner, Barbara; Banafsche, Ramin; Pichlmaier, Maximilian; Tsilimparis, Nikolaos
Purpose: To present a novel technique to successfully cross a mechanical aortic valve prosthesis. Technique: A 55-year-old female patient with genetically verified Marfan syndrome presented with a 5-cm anastomotic aneurysm of the proximal aortic arch after previous ascending aortic replacement due to a type A aortic dissection in 2007. The patient also underwent mechanical aortic valve replacement in 1991. A 3-stage hybrid repair was planned. The first 2 steps included debranching of the supra-aortic vessels. In the third procedure, a custom-made double branched endovascular stent-graft with a short 35-mm introducer tip was implanted. The mechanical valve was passed with the tip of the dilator on the lateral site of the leaflet, without destructing the valve and with only mild symptoms of aortic insufficiency, as one leaflet continued to work. This allowed the implantation of the stent-graft directly distally of the coronary arteries. Postoperative computed tomography angiography showed no endoleaks and patent coronary and supra-aortic vessels. Conclusion: Passing a mechanical aortic valve prosthesis at the proper position is feasible and allows adequate endovascular treatment in complex arch anatomy. However, caution should be taken during positioning of the endovascular graft as the tip may potentially damage the valve prosthesis.